The relationship between core strength and performance in Division I female soccer players - Nesser, T. W.; Lee, W. L. (Journal of Exercise Physiology online, 2009)
To identify relationships between core stability and various strength and power variables in division I female soccer players. 16 NCAA division I female soccer players (height 163.6 cm ± 5.2 cm, weight 60.7 kg ± 7.5 kg) completed strength and performance testing prior to off-season conditioning. Subjects were tested on two strength variables (1RM bench press, and 1RM squat), three performance variables (countermovement vertical jump, 40 yard sprint, and a 10 yard shuttle run), and core strength (back extension, trunk flexion, and left and right bridge). No significant correlations were identified between core strength and strength and power. The results of this study suggest core strength is not related to strength and power. Core strength does not contribute significantly to strength and power and should not be the focus of any strength and conditioning program with the intent to improve sport performance. ABSTRACT FROM AUTHOR